2022
DOI: 10.1039/d2fo00051b
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccessibility and intestinal cell uptake of carotenoids and chlorophylls differ in powdered spinach by the ingredient form as measured using in vitro gastrointestinal digestion and anaerobic fecal fermentation models

Abstract: Insights into food matrix factors impacting bioavailability of bioactive carotenoids and chlorophylls from fruits and vegetable ingredients are essential to understanding their ability to promote health. Stability and bioaccessibility of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…It is worth to note that, in all of our experimental set-ups, pH was not controlled nor set at a specific value beyond the initial pH. Although our fermentation is tamponed, previous literature using our ex vivo – in vitro fermentation method has shown that digested spinaches 26 and grape juices 27 can reduce fermentation pH to 6.0 within a 45 h fermentation window of time. This factor could affect the reported bioactivity of undigested beverages, and digested beverages and their fractions.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth to note that, in all of our experimental set-ups, pH was not controlled nor set at a specific value beyond the initial pH. Although our fermentation is tamponed, previous literature using our ex vivo – in vitro fermentation method has shown that digested spinaches 26 and grape juices 27 can reduce fermentation pH to 6.0 within a 45 h fermentation window of time. This factor could affect the reported bioactivity of undigested beverages, and digested beverages and their fractions.…”
Section: Discussionmentioning
confidence: 99%